2006
DOI: 10.3354/meps318031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic bottom trawling alters the functional composition of benthic invertebrate communities on a sea-basin scale

Abstract: Bottom trawling causes widespread physical disturbance of sediments in seas and oceans and affects benthic communities by removing target and non-target species and altering habitats. One aspiration of the ecosystem approach to management is to conserve function as well as biodiversity, but trawling impacts on benthic community function need to be understood before they can be managed. Here we present the large scale and long term impact of chronic trawling on the functional composition of benthic invertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
231
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(246 citation statements)
references
References 56 publications
8
231
2
5
Order By: Relevance
“…Given the findings elsewhere that report higher mortality of suspension feeders at locations that are subject to fishing activity (e.g. Tillin et al 2006;van Denderen et al 2015), it is surprising that we found a higher ratio of suspension to deposit feeders in sand communities that experienced a higher frequency of chronic fishing. However, a clear trend that emerges from previous studies is that the degree of natural disturbance in which a community develops determines the degree to which it is affected by bottom fishing (Kaiser and Spencer 1996;Hiddink et al 2006;Sciberras et al 2013).…”
Section: Discussioncontrasting
confidence: 43%
“…Given the findings elsewhere that report higher mortality of suspension feeders at locations that are subject to fishing activity (e.g. Tillin et al 2006;van Denderen et al 2015), it is surprising that we found a higher ratio of suspension to deposit feeders in sand communities that experienced a higher frequency of chronic fishing. However, a clear trend that emerges from previous studies is that the degree of natural disturbance in which a community develops determines the degree to which it is affected by bottom fishing (Kaiser and Spencer 1996;Hiddink et al 2006;Sciberras et al 2013).…”
Section: Discussioncontrasting
confidence: 43%
“…Over the past decades, the impacts of major anthropogenic pressures on coastal and benthic marine biodiversity have been studied intensely. Here, especially field assessments investigated the negative effects arising from bottom trawling (Jennings and Kaiser 1998;Kaiser et al 2006;Tillin et al 2006;Worm et al 2006;Olsgard et al 2008), coastal nutrient loading (Rosenberg and Nilsson 2005;Quijon et al 2008), and climate change (Norderhaug et al 2015). However, since many of these drivers act on the ecosystems simultaneously and over long periods of time Halpern et al 2008), it is difficult to infer cumulative impacts from such assessments (Moksnes et al 2008;Robinson and Frid 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The overexploitation of marine resources has been recognized to cause drastic impairments of the food web structure and the consequent alteration of the productivity (Pauly & Christensen, 1995). Besides, fishing has dramatic effects on the non-target species, and the different techniques employed have been proved to cause a wide range of alterations to biodiversity and community structure (Jennings et al, 2001;Queirós et al, 2006;Tillin et al, 2006). These aspects are reflected, for example, by the pronounced imbalance in terms of damage, physiological stress, and survival among the species subjected to trawling activities.…”
Section: Introductionmentioning
confidence: 99%